Meta-Analysis: Effect of Acupuncture Therapy in Lowering Frozen Shoulder Pain - Mehdya Vikia Murti; Hanung Prasetya; Rita Benya Adriani (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: Acupuncture therapy has become a popular non-drug therapy with good curative effects, convenient application, non-toxic side effects, and low cost, and it has been widely used in the treatment of Frozen Shoulder. This study aims to analyze and estimate the effect of acupuncture therapy on reducing the degree of pain in Frozen shoulders. Subjects and Method: This study used a systematic review and meta-analysis by following PICO, Population: Frozen Shoulder patients. Intervention: acupuncture therapy. Comparison: no acupuncture therapy. Result: reduction in the degree of Frozen shoulder pain. The data used was obtained from scientific research articles from electronic databases including PubMed, Google Scholar, Hindawi, BMC, Scopus, and Science Direct Randomized Control Trial (RCT) designs from 2011 to 2022 which report effect sizes with mean and SD. The keywords used in the search for scientific articles are “Acupuncture” AND “Frozen Shoulder” AND “Frozen Shoulder Pain”. The selection of articles was carried out using the PRISMA flowchart. Data were analyzed using Review Manager software version 5.4.1. Results: A total of 9 articles with eligible RCT designs from Asia and Europe were selected for the systematic review and meta-analysis. The results of the meta-analysis showed that patients with Frozen Shoulders who received acupuncture therapy experienced a degree of pain 0.48 units lower than without acupuncture and was statistically significant (SMD= -0.48; 95% CI= -1.14 to -0.18; p=0.15). Conclusion: Acupuncture therapy reduces the degree of Frozen Shoulder pain. Keywords: acupuncture, pain, frozen shoulder. Correspondence: Mehdya Vikia Murti. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta, Central Java 57126. Email: mehdyvikiamurti@gmail.com. Mobile: +62895363037033.